2013
DOI: 10.1111/1365-2478.12072
|View full text |Cite
|
Sign up to set email alerts
|

Optimized arrays for 2D cross‐borehole electrical tomography surveys

Abstract: The use of optimized arrays generated using the 'Compare R' method for cross-borehole resistivity measurements is examined in this paper. We compare the performances of two array optimization algorithms, one that maximizes the model resolution and another that minimizes the point spread value. Although both algorithms give similar results, the model resolution maximization algorithm is several times faster. A study of the point spread function plots for a cross-borehole survey shows that the model resolution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Figure 1 shows that the PSF and the radius of resolution independently mark out a circular area of approximately the same size around the cell of investigation and thereby emphasizes the validity of the common approach to only use the diagonal entries as a quantitative measure of resolution. This is in agreement with the recent finding of Loke et al (2014), who demonstrated that optimizations of individual four-point configurations based on PSF measures do not notably improve the information content of the resulting arrays compared to optimizations based exclusively on the diagonal entries, while the former is computationally considerably more cumbersome. Yet it should be emphasized that the comparable performances of the diagonal entries and PSF measures during array optimizations are by no means evidence of their equality.…”
Section: Image Appraisal and Experimental Designsupporting
confidence: 92%
See 2 more Smart Citations
“…Figure 1 shows that the PSF and the radius of resolution independently mark out a circular area of approximately the same size around the cell of investigation and thereby emphasizes the validity of the common approach to only use the diagonal entries as a quantitative measure of resolution. This is in agreement with the recent finding of Loke et al (2014), who demonstrated that optimizations of individual four-point configurations based on PSF measures do not notably improve the information content of the resulting arrays compared to optimizations based exclusively on the diagonal entries, while the former is computationally considerably more cumbersome. Yet it should be emphasized that the comparable performances of the diagonal entries and PSF measures during array optimizations are by no means evidence of their equality.…”
Section: Image Appraisal and Experimental Designsupporting
confidence: 92%
“…Friedel, 2003). Despite the drawback of being computationally expensive, the model resolution is the preferred choice in ERT experimental design studies and has proven to be a good forecaster of the eventual inversion performance (Stummer et al, 2004;Coscia et al, 2008;Wilkinson et al, 2006Wilkinson et al, , 2010Wilkinson et al, , 2012Loke et al, 2014). Individual columns of R m , so called point spread functions (PSF), show how a resistivity perturbation in the subsurface is mapped into the final inversion image (Oldenborger and Routh, 2009).…”
Section: Image Appraisal and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acquiring all of these electrode arrangements is prohibitively time-consuming and does not guarantee a superior outcome. Optimized arrays, with trade-offs between acquisition efficiency and optimum ERI resolution, is an active field of research for ERI imaging (e.g., Loke et al 2014aLoke et al , b, 2015bStummer et al 2002;Szalai et al 2013;Wilkinson et al 2012Wilkinson et al , 2006. Several methods of optimization exist; however, the analysis of resolution matrices has proven popular.…”
Section: Background: Electrical Resistivity Imagingmentioning
confidence: 99%
“…The sides of the model used to calculate the resolution values are extended 4 m in both the x and y directions beyond the edges of the survey grid. This is to ensure that all the regions of the subsurface that have significant resolution values are included (Loke et al 2014a). The subsurface is subdivided into model cells with widths of 1 m in both the x and y directions.…”
Section: Model Resolution Sectionsmentioning
confidence: 99%